Coping with brief periods of food restriction: mindfulness matters - Paolini, Brielle (Frontiers Media S.A., 2012)
The obesity epidemic had spawned considerable interest in understanding peoples' responses to palatable food cues that are plentiful in obesogenic environments. In this paper we examine how trait mindfulness of older, obese adults may moderate brain networks that arise from exposure to such cues. Nineteen older, obese adults came to our laboratory on two different occasions. Both times they ate a controlled breakfast meal and then were restricted from eating for 2.5 h. After this brief period of food restriction, they had an fMRI scan in which they were exposed to food cues and then underwent a 5 min recovery period to evaluate brain networks at rest. On one day they consumed a BOOST® liquid meal prior to scanning, whereas on the other day they only consumed water (NO BOOST® condition). We found that adults high in trait mindfulness were able to return to their default mode network (DMN), as indicated by greater global efficiency in the precuneus, during the post-exposure rest period. This effect was stronger for the BOOST® than NO BOOST® treatment condition. Older adults low in trait mindfulness did not exhibit this pattern in the DMN. In fact, the brain networks of those low on the MAAS suggests that they continued to be pre-occupied with the elaboration of food cues even after cue exposure had ended. Further work is needed to examine whether mindfulness-based therapies alter brain networks to food cues and whether these changes are related to eating behavior.